THE EFFECTS OF IDENTITY SHIFT FOR ENGLISH SKILL STUDENTS’ STUDY ABROAD: PHOTOVOICE STUDY - Nur Khofifah Saadiah; Alan Jaelani (La Tansa Mashiro, 2022)
There are many universities holding an exchange program for helping students improve their English skill and create identity shift. This research aims to know what identity shift students’ study abroad experience and to know the effects of identity shift on students’ study abroad. The researcher uses a qualitative method in this research. Photovoice task and in-depth interviews are used to get the data. The respondents of this research are eleven students who joined the study abroad program. It is concluded that there is an identity shift in themselves. The researcher found the effects of the identity shift of students’ study abroad such as the respondents speak English more, understand different accents, and give respect to different cultures. Therefore, by joining a study abroad program, they can increase their confidence and improve their English skills.